Plant bioactive compounds affecting biomarkers and final outcome of COVID-19 - Gjorgieva Ackova, Darinka; Maksimova, Viktorija; Smilkov, Katarina (Archives of Pharmacy, 2022)
Herbal medicinal products are known for their widespread use toward various viral infections and ease of disease symptoms. Therefore, the sudden appearance of the Severe Acute Respiratory Syndrome-related Coronavirus 2 (SARS-CoV-2) and COVID-19 disease was no exception. Bioactive compounds from natural plant origin could act on several disease levels: through essential immunological pathways, affecting COVID-19 biomarkers, or by halting or modulating SARS-CoV-2. In this paper, we review the recently published data regarding the use of plant bioactive compounds in the prevention/treatment of COVID-19. The mode of actions responsible for these effects is discussed, including the inhibition of attachment, penetration and release of the virus, actions affecting RNA, protein synthesis and viral proteases, as well as other mechanisms. The reviewed information suggests that plant bioactive compounds can be used alone or in combinations, but upcoming, extensive and global studies on several factors involved are needed to recognize indicative characteristics and various patterns of bioactive compounds use, related with an array of biomarkers connected to different elements of inflammatory and immune-related processes of COVID-19 disease.